Novel Antennapedia and Ultrabithorax trimeric complexes with TBP and Exd regulate transcription - Alely Villarreal-Puente; Claudia Altamirano-Torres; Gustavo Jiménez-Mejía; Carolina Hernández-Bautista; Rubén Montalvo-Méndez; Martha Vázquez; Mario Zurita; Diana Reséndez-Pérez (Hereditas, 2024)
Abstract Background Hox proteins interact with DNA and many other proteins, co-factors, transcriptional factors, chromatin remodeling components, non-coding RNAs and even the extracellular matrix that assembles the Hox complexes. The number of interacting partners continues to grow with diverse components and more transcriptional factors than initially thought. Hox complexes present many activities, but their molecular mechanisms to modulate their target genes remain unsolved. Results In this paper we showed the protein-protein interaction of Antp with Ubx through the homeodomain using BiFC in Drosophila. Analysis of Antp-deletional mutants showed that AntpHD helixes 1 and 2 are required for the interaction with Ubx. Also, we found a novel interaction of Ubx with TBP, in which the PolyQ domain of TBP is required for the interaction. Moreover, we also detected the formation of two new trimeric complexes of Antp with Ubx, TBP and Exd using BiFC-FRET; these proteins, however, do not form a trimeric interaction with BIP2 or TFIIEβ. The novel trimeric complexes reduced Antp transcriptional activity, indicating that they could confer specificity for repression. Conclusions Our results increase the number of transcriptional factors in the Antp and Ubx interactomes that form two novel trimeric complexes with TBP and Exd. We also report a new Ubx interaction with TBP. These novel interactions provide important clues of the dynamics of Hox-interacting complexes involved in transcriptional regulation, contributing to better understand Hox function.